Light-modulated 8-Pmmn borophene-based pure crossed Andreev reflection - Renxiang Cheng; Mengying Li; Hong Wang; Yafang Xu; Xing’ao Li; Xingfei Zhou (New Journal of Physics)
We investigate the off-resonant circularly polarized light-modulated crossed Andreev reflection (CAR) in an 8-Pmmn borophene-based normal conductor/superconductor/normal conductor junction. When the signs of Fermi energies in two normal regions are opposite, the pure CAR without the local Andreev reflection and the elastic cotunneling occurs. By using the Dirac–Bogoliubov–de Gennes equation and the Blonder–Tinkham–Klapwijk formula, the pure CAR conductance and its oscillation as a function of the junction length and the Fermi energy in the superconducting regions are discussed. It is found that the value of pure CAR conductance peak value and its corresponding value of light-induced gap increase with the increase of incident energy of electron. Furthermore, the valley splitting for the transmitted hole is found due to the presence of tilted velocity of borophene. Our findings are beneficial for designing the high efficiency 8-Pmmn borophene-based nonlocal transistor and nonlocal valley splitter without local and non-entangled processes.